2004
DOI: 10.1172/jci200420935
|View full text |Cite
|
Sign up to set email alerts
|

Specific induction of neuronal cells from bone marrow stromal cells and application for autologous transplantation

Abstract: Bone marrow stromal cells (MSCs) have the capability under specific conditions of differentiating into various cell types such as osteocytes, chondrocytes, and adipocytes. Here we demonstrate a highly efficient and specific induction of cells with neuronal characteristics, without glial differentiation, from both rat and human MSCs using gene transfection with Notch intracellular domain (NICD) and subsequent treatment with bFGF, forskolin, and ciliary neurotrophic factor. MSCs expressed markers related to neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
275
3
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 552 publications
(292 citation statements)
references
References 35 publications
(13 reference statements)
6
275
3
2
Order By: Relevance
“…Brain tissue sections examination indicated that single infusion with BM-MSCs resulted in intact histological structure of the striatum. This finding coincides with Dezawa et al [84] who reported that nerve system recovery after BM-MSCs transplantation could be related to their secretion of neurotrophic factors that restore the function of nervous system, promotion of local angiogenesis and vascular reconstruction and neuronal regeneration through promotion of autologous neuronal regeneration and differentiation of transplanted cells into neural cells.…”
Section: Discussionsupporting
confidence: 91%
“…Brain tissue sections examination indicated that single infusion with BM-MSCs resulted in intact histological structure of the striatum. This finding coincides with Dezawa et al [84] who reported that nerve system recovery after BM-MSCs transplantation could be related to their secretion of neurotrophic factors that restore the function of nervous system, promotion of local angiogenesis and vascular reconstruction and neuronal regeneration through promotion of autologous neuronal regeneration and differentiation of transplanted cells into neural cells.…”
Section: Discussionsupporting
confidence: 91%
“…For neurogenesis, various inducers, alone or in combination, are involved in neurocytic differentiation in vitro of MSCs. These include retinoic acid (Cho et al, 2005), DMSO and BHA (Chu et al, 2004;Lu et al, 2004), GM1 and bFGF (Dezawa et al, 2004;Zhang et al, 2004b;Munoz-Elias et al, 2003), and 2-mercaptoethanol (2-ME) (Guo et al, 2001). It was suggested that cAMP signaling pathway should be involved in neurocytic differentiation of MSCs (Suon et al, 2004;Jori et al, 2005), but it could not rule out the synergistic effect of other signaling pathways on neurogenesis of hMSCs, in regard to neural differentiation of embryonic stem cells (Kleber et al, 2005;Bainter et al, 2001;Otero et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The MSCinducible cell types include endothelial cells (Oswald et al 2004), cardiac muscle cells (Makino et al 1999), skeletal muscle cells (Dezawa et al 2005), hepatocytes (Oyagi et al 2006;Prindull and Zipori 2004;Snykers et al 2009), neuronal cells (Dezawa et al 2004;Wislet-Gendebien et al 2005), peripheral glial cells (Dezawa et al 2001) and insulin-producing cells (Phinney and Prockop 2007) and epithelial cell (Spees et al 2003) (Fig. 1).…”
Section: Differentiation Ability Of Mscsmentioning
confidence: 99%
“…Granted that MSCs are a heterogeneous cell population, MSCs as a whole show differentiation not only into the same mesodermal lineage cells of osteocytes, chondrocytes, and adipocytes, but also into other lineages such as into neuronal cells (ectoderm) and hepatocytes (endoderm) (Dezawa et al 2001(Dezawa et al , 2004(Dezawa et al , 2005Pittenger et al 1999). For this reason, MSCs are considered pluripotent cells.…”
Section: Are Mscs Pluripotent Stem Cells?mentioning
confidence: 99%
See 1 more Smart Citation